The Effectiveness of Face Poly Media in Enhancing Computational Thinking Skills in Early Childhood - Andi Nur Maharani Islami (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aims to determine the effectiveness of Face Poly media in developing computational thinking skills in early childhood aged 5–6 years at TK Telkom Makassar. Preliminary observations at TK Telkom Makassar indicated that learning media used were still conventional and less stimulating, resulting in children’s limited ability to recognize patterns, decompose problems, and think algorithmically. This research employed a pre-experimental One-Group Pretest-Posttest Design, providing treatment in the form of structured Face Poly media activities and then comparing children’s computational thinking abilities before and after the intervention. The sample consisted of class B1, totalling 16 children aged 5–6 years. Data were collected using a checklist observation sheet covering four core computational thinking indicators: decomposition, pattern recognition, abstraction, and algorithmic thinking. Data were analyzed using the paired sample T-test. The results showed tₘₑₜ > tₜₐₗₑ or 32.940 > 1.753, indicating that H₀ is rejected and Hₐ is accepted. A significance value of 0.000 (< 0.05) confirms that Face Poly media is effective in developing computational thinking skills in children aged 5–6 years at TK Telkom Makassar.